Occurrence and Toxicogenetic Profiling of Clostridium perfringens in Buffalo and Cattle: An Update from Pakistan - Muhammad Umar Zafar Khan; Muhammad Humza; Shunli Yang; Mughees Aizaz Alvi; Muhammad Zahid Iqbal; Hafiza Zain-ul-Fatima; Shumaila Khalid; Tahir Munir; Jianping Cai (Toxins, 2021)
Clostridium perfringens is a Gram-positive bacterium that possess seven toxinotypes (A, B, C, D, E, F, and G) that are responsible for the production of six major toxins, i.e., α, β, ε, ι, CPE, and NetB. The aim of this study is to find out the occurrence of toxinotypes in buffalo and cattle of Punjab province in Pakistan and their corresponding toxin-encoding genes from the isolated toxinotypes. To accomplish this aim, six districts in Punjab province were selected (i.e., Lahore, Sahiwal, Cheecha Watni, Bhakkar, Dera Ghazi Khan, and Bahawalpur) and a total of 240 buffalo and 240 cattle were selected for the collection of samples. From isolation and molecular analysis (16S rRNA), it was observed that out of seven toxinotypes (A–G), two toxinotypes (A and D) were found at most, whereas other toxinotypes, i.e., B, C, E, F, and G, were not found. The most frequently occurring toxinotype was type A (buffalo: 149/240; cattle: 157/240) whereas type D (buffalo: 8/240 cattle: 7/240) was found to occur the least. Genes encoding toxinotypes A and D were cpa and etx, respectively, whereas genes encoding other toxinotypes were not observed. The occurrence of isolated toxinotypes was studied using response surface methodology, which suggested a considerable occurrence of the isolated toxinotypes (A and D) in both buffalo and cattle. Association between type A and type D was found to be significant among the isolated toxinotypes in both buffalo and cattle (p ≤ 0.05). Correlation was also found to be positive and significant between type A and type D. C. perfringens exhibits a range of toxinotypes that can be diagnosed via genotyping, which is more reliable than classical toxinotyping.